Analisis Maqashid Syari'ah Terhadap Kategorisasi Program Beasiswa Cendekia BAZNAS sebagai Instrumen Zakat Produktif: Studi Kasus pada BAZNAS Kota Tangerang Selatan - Khairunnisa, Salsabila; Irawan, Anggi; Anggraini, Rizki Dwi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
BAZNAS's Cendekia Scholarship Program is a form of productive zakat utilization that does not generate direct economic benefit, raising the conceptual question of whether an education-based program of this kind can still be categorized as productive zakat. This study analyzes the categorization of the Cendekia Scholarship Program at BAZNAS South Tangerang City as an instrument of productive zakat through the perspective of maqashid syariah. It employs an empirical juridical qualitative approach, with data collected through observation, interviews with one program staff member and two scholarship recipients, and documentation of fund distribution reports, analyzed using triangulation. The findings show that the program fulfills four indicators of productive zakat, namely sustainable empowerment, human capital, asset building, and the transformation of mustahik into muzaki, even though its economic benefits only materialize after recipients complete their education and begin working. From the maqashid syariah perspective, the program is also aligned with two central dimensions: hifzh al-aql, through the development of recipients' academic capacity and competence, and hifzh al-mal, through the economic stability of alumni who have started paying zakat or infaq after being employed. The study concludes that the success of productive zakat should not be measured solely by short-term financial benefits, but also by long-term investment in human quality that contributes to overall welfare and the fulfillment of syariah objectives.